TMS assessment of corticospinal tract integrity after stroke: broadening the concept to inform neurorehabilitation prescription - Kumar, Sapna; Ferraro, Mary; Nguyen, Lienhoung; Cao, Ning; Ung, Nathaniel; Jose, Joshua S.; Weidenauer, Cheryl; Edwards, Dylan J.; Mayer, Nathaniel H. (Frontiers in Human Neuroscience, 2024)
Upper limb actions require intersegmental coordination of scapula, shoulder, elbow, forearm, wrist and hand muscles. Stroke hemiparesis, presenting as impairment of intersegmentally coordinated voluntary movement, is associated with altered integrity of corticospinal tract (CST) transmission from motor cortex (M1) to muscles. Motor Evoked Potentials (MEPs) elicited by M1 TMS of “at rest” muscles, or as a back-up, during muscle contraction, has been used to identify CST integrity and predict outcome after hemiparesis, under the implicit assumption that MEP presence in only one or two muscles are manifest surrogates of CST integrity for other muscles of the upper limb. This paper describes a method of applying TMS during motor tasks that span proximal and distal muscles, evaluating multi-muscle electromyography (EMG) and MEPs across all task-relevant limb segments. Protocols are presented for assessing voluntary motor behavior in hemiparetic stroke using isometric, unimanual, bimanual and ‘REST’ conditions that broaden the concept of the degree of CST integrity in order to inform clinical prescription for neurorehabilitation, and is to be differentiated from a potential prognostic role. Data describing multi-muscle TMS-MEP recordings will be presented in a case of subacute hemiparetic stroke to elucidate our perspective.